2006
DOI: 10.1007/s10815-006-9054-0
|View full text |Cite
|
Sign up to set email alerts
|

Is a lower dose of cetrorelix acetate effective for prevention of LH surge during controlled ovarian hyperstimulation?

Abstract: This study demonstrates that a daily dose of cetrorelix 0.2 mg is able to prevent premature LH surge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…Cetrorelix suppressed estrogen, progesterone, and testosterone levels in female rats (Horvath et al, ). Cetrorelix suppresses testosterone in postmenopausal women (Chantler, Gordon, Millan, & Panarelli, ; Pechstein et al, ) and estrogen levels in women undergoing controlled ovarian hyperstimulation (Buchter et al, ; Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetrorelix suppressed estrogen, progesterone, and testosterone levels in female rats (Horvath et al, ). Cetrorelix suppresses testosterone in postmenopausal women (Chantler, Gordon, Millan, & Panarelli, ; Pechstein et al, ) and estrogen levels in women undergoing controlled ovarian hyperstimulation (Buchter et al, ; Chen et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In premenopausal women, leuprolide and cetrorelix suppress LH and FSH levels (Larmore & Klein, 2000;Pechstein et al, 2000). Single dose administration of not only cetrorelix but also leuprolide reduces LH level in rats after 7 days of treatment (Chen et al, 2006;Murase et al, 2005). This may be due to continuous administration of GnRH-agonist-mediated downregulation of receptor and suppression of gonadotropin secretion (Magon, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In other words, if the live birth rates were not affected, any protocols that use the least amount of GnRH antagonist would be less costly. Under the background of decreasing exposure to GnRH antagonist, Chen et al showed that a daily dose of 0.2 mg cetrorelix acetate was effective to prevent premature LH surge with comparable clinical pregnancies ( 29 ). Other researcher revealed that alternate-day administration of ganirelix was as effective as daily injections in preventing premature luteinization with similar clinical pregnancy rate ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…The present study obtained LH a surge suppression using a novel GnRH-antagonist protocol with a lower dose of cetrorelix (0.125 mg) starting on the evening of Day 5 of ovarian stimulation, and increased to 0.250 mg once an appropriate follicular size was reached. In addition, the mean amount of cetrorelix administered per patient in this study, 0.9 mg, was less than the 1.0 mg used in one of the previous trials of 0.20 mg in a fixed scheme [11]. To the best of our knowledge, the treatment protocol in this study used the lowest dose of GnRH antagonist reported in clinical trials.…”
Section: Discussionmentioning
confidence: 60%
“…Previous studies demonstrated that a fixed scheme of 0.20 mg/day of cetrorelix was effective in preventing a premature LH surge regardless of follicular size [11,12]. The present study obtained LH a surge suppression using a novel GnRH‐antagonist protocol with a lower dose of cetrorelix (0.125 mg) starting on the evening of Day 5 of ovarian stimulation, and increased to 0.250 mg once an appropriate follicular size was reached.…”
Section: Discussionmentioning
confidence: 62%